The Influence of Welding Ampere Range to ST-40 Shear Strength with Butt Joint - Rudi Winarno; Daryono Daryono; Moh. Jufri (University of Muhammadiyah Malang, 2018)
This experiment was conducted on the influence of welding process with ampere range variation and weld joints toward ST-40 shear strength. Furthermore, welded specimen is tested with tensile test. Method of this experiment is testing shear strength by using tensile testing machine where each five-specimens were previously welded by ampere range of 80 A, 90 A, and 100 A. Shear results show the highest shear strength is on 128.4916 N/mm2 with 80-ampere range on specimen no. 5, while on 90-ampere range variation the highest shear strength is on 124.7528 N/mm2, the specimen no. 5. Meanwhile, on 100-ampere range variation, the highest shear strength is on 120.1484 N/mm2, the specimen no. 4. The higher ampere (I) used, the higher heat (Q) resulted. When the heat increases, the welding electrode is perfectly fused. It makes good welding result achieved. The more strength on welding result, the higher shear strength (τ) achieved. On the other hand, the higher ampere range on welding process results higher shear strength.